PEMAHAMAN TEKSTUAL DAN KONTEKSTUAL PAKAR HADIS DAN PAKAR FIKIH SEPUTAR SUNNAH NABI (Studi Kritis atas Pemikiran Syaikh Muhammad Al-Ghazali) - Dr. Mukhlis Mukhtar (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2015)
Muhammad al-Ghazali was a scientist and muballig very critical in exploring the teachings of Islam. He positioned the Qur’an as the source of the first and foremost in Islam so that the hadith (traditions matn) should be in line with the Qur’an, if not he leave even though his sanad valid. In understanding the verse or hadith, he is absolutely adhered to the textual, but on certain things so that he also uses contextual verse or hadith is not understood partially.